Screening for covalent inhibitors using DNA-display of small molecule libraries functionalized with cysteine reactive moieties12. Issue 7 (30th June 2016) - Zambaldo, C.; Daguer, J.-P.; Saarbach, J.; Barluenga, S.; Winssinger, N.
Abstract : Discriminating between non-covalent and covalent inhibitors with SDS wash in microarray-based screen. Abstract : DNA-encoded chemical libraries are increasingly used to identify leads for drug discovery or chemical biology. Despite the resurging interest in covalent inhibitors, libraries are typically designed with synthon filtered out for reactive functionalities that can engage a target through covalent interactions. Herein, we report the synthesis of two libraries containing Michael acceptors to identify cysteine reactive ligands. We developed a simple procedure to discriminate between covalent and high affinity non-covalent inhibitors using DNA display of the library in a microarray format. The methodology was validated with known covalent and high affinity non-covalent kinase inhibitors. Screening of the library revealed novel covalent inhibitors for MEK2 and ERBB2.